Mobile-Assisted Instructional for Domestic Maid (MAID-M) - Teh, Phoey Lee *; Muketha, Geoffrey Muchiri; Gu, Yin Xin (Little Lion Scientific; JATIT, 2014)
Statistics from Immigration Department of Malaysia has shown that the foreign workers have increased tremendously over the past 4 years. Different nationalities of foreign maids usually speak in their own mother languages from their home countries. A certain level of communication barrier between the Malaysia’s employers and the foreign workers were identified in the previous study. The misunderstanding of tasks requested to their domestic maid had led to the communication barrier. The study confirmed positively that this communication barrier has occurred between the employer and the maid. In this paper, the Mobile-Assisted Instructional for Domestic Maid (MAID-M) is proposed and presented both conceptually and physically. Feedbacks of the proposed application is collected and tested.